PICTO TEXTUAL GLOSSES IN TEACHING VOCABULARY - Anita Fitria Nurwulan; Sobari Sobari (PROJECT (Professional Journal of English Education), 2020)
The purpose of this research is to know english vocabulary mastery incresed by using picto textual glossesin every meeting in class. The object of this research is 8th grade students in Mutiara 1 junior high school. the main focus in teaching english is to improving students english vocabulary mastery . By improving vocabulary mastery, students will be improving english material easier. The data in this research come from interaction between teacher and students in learning process and it is as students learning activity in the class. the research instruments used test questions.The method of data collecting of the resarch is by using pretest-treatment-postest in the class.  Based on pre test and post test, they showed some improvement on process of get new vocabulary from learning with that method. . The result or the conclusion can be got from the resarch by using picto textual glosses method, data from pre test and post test showed that there were some benefits of picto textual glosses method: 1. Develop of students’ memory ability to increasing vocabulary, 2. Having a fun learning situation. The data showed HI is accepted, because Asymp. Sig. (2-tailed) worth 0,000. because the value of  0,000 is smaller; of, <0.05. Keywords:  Vocabulary, Vocabulary mastery, Picto textual glosses, SMP Mutiara I, 8th grade.